(untitled) (Research, Society and Development, 2023)
The present paper carried out an integrative review about the clinical studies on Hibiscus sabdariffa L., as a therapeutic alternative in the treatment of obesity. This is an integrative literature review, carried out in 6 phases that consisted of: i) identification of the theme; ii) formulation of the guiding question; iii) literature search; iv) categorization of the studies found; v) analysis of included studies and vi) interpretation of results. The search for articles was carried out through the BVS, SCIELO and PubMed databases, using the descriptors “Hibiscus sabdariffa”, “medicinal plants”, “obesity”, “clinical studies”, linked by the Boolean operators “AND” and “OR”. Initially, 11 articles were found, which after applying the inclusion and exclusion criteria, resulted in 3 analyzed articles. The results showed that the extract with HS reduces body weight, BMI, body fat, as well as decreases the distribution of abdominal fat in several female and male patients at different ages, as well as reduced diastolic and systolic pressures. Another relevant finding was the association between HS and LC, the results revealed a significant difference in anthropometric parameters in patients treated with both plants. Thus, it is concluded that the use of HS as a therapeutic alternative in the treatment of obesity is viable and effective, and that when associated with LC, the anthropometric effects are enhanced.